2019
DOI: 10.1063/1.5114881
|View full text |Cite
|
Sign up to set email alerts
|

The significance of grain morphology and moisture content on the response of silica sand to ballistic penetration

Abstract: The dynamic response of sand is of interest for a wide range of applications, from civil engineering to asteroid impact, in addition to defense and industrial processes. Granular dynamics are controlled by a complex network of inter-grain force chains, yet our understanding of how grain morphology, moisture, rate and loading geometry affect the response to rapid compaction remains limited. Here, we show how just 1% moisture can significantly reduce penetration resistance in silica sand, while smoother-grained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Due to the granular structure of sand, it tends compact and densify when it is under a compressive load [1,6,39]. Previous studies have shown a change in the energy absorption behaviour of sand as its density changes, thus implying a shift in its penetration resistance [3,7]. The plate was placed in the sandbag so that it was not impacted by the projectile given the timescale of the simulation.…”
Section: Compaction Behaviour Of Sandmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the granular structure of sand, it tends compact and densify when it is under a compressive load [1,6,39]. Previous studies have shown a change in the energy absorption behaviour of sand as its density changes, thus implying a shift in its penetration resistance [3,7]. The plate was placed in the sandbag so that it was not impacted by the projectile given the timescale of the simulation.…”
Section: Compaction Behaviour Of Sandmentioning
confidence: 99%
“…The major threat from blast is the propagation of the shockwave through the material [4,5]. Sand resists blast by undergoing densification due to the pressure load from the shockwave [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations